Improving efficiency of industrial maintenance with context aware adaptive authoring in augmented reality - Erkoyuncu, John Ahmet; Fernández del Amo, Iñigo; Roy, Rajkumar; Dalle Mura, Michela; Dini, Gino (Elsevier, 2017)
Efficiency of industrial maintenance operation is significantly dependent on the skill and practice of the technicians involved. This paper demonstrates a novel approach to improve the maintenance efficiency through adaptive operational support using a context aware Augmented Reality (AR) technique that adapts with available data and the skill level of the technicians and without the need for prior working knowledge of AR. The AR system can be dynamically adapted by non-programmer maintenance technicians to improve the efficiency further.
Keywords: Augmented reality; Maintenance; Adaptive authoring